Inactivation of Lrp5 in Osteocytes Reduces Young’s Modulus and Responsiveness to the Mechanical Loading - Zhao, Liming (2013)
Low-density-lipoprotein receptor-related protein 5 (Lrp5) is a co-receptor in Wnt signaling, which plays a critical role in development and maintenance of bone. Osteoporosis-pseudoglioma syndrome, for instance, arises from loss-of- function mutations in Lrp5, and global deletion of Lrp5 in mice results in significantly lower bone mineral density. Since osteocytes are proposed to act as a mechanosensor in bone, we addressed a question whether a conditional loss-of-function mutation of Lrp5 selective to osteocytes (Dmp1-Cre; Lrp5(f/f)) would alter responses to ulna loading. Loading was applied to the right ulna for 3 min (360 cycles at 2 Hz) at a peak force of 2.65 N for 3 consecutive days, and the contralateral ulna was used as a non-loaded control. Young’s modulus was determined using a midshaft section of the femur. The results showed that compared to age-matched littermate controls, mice lacking Lrp5 in osteocytes exhibited smaller skeletal size with reduced bone mineral density and content. Compared to controls, Lrp5 deletion in osteocytes also led to a 4.6-fold reduction in Young’s modulus. In response to ulna loading, mineralizing surface, mineral apposition rate, and bone formation rate were diminished in mice lacking Lrp5 in osteocytes by 52%, 85%, and 69%, respectively. Collectively, the results support the notion that the loss-of-function mutation of Lrp5 in osteocytes causes suppression of mechanoresponsiveness and reduces bone mass and Young’s modulus. In summary, Lrp5-mediated Wnt signaling significantly contributes to maintenance of mechanical properties and bone mass.